Therapeutic role of dietary nitrates on cardiorespiratory function in cancer survivors - Turpin, Vanessa-Rose Garcia (Kansas State University, 2020)
Introduction: The acute and chronic adverse physiological consequences of anticancer therapy include direct injury to the entire cardiovascular-skeletal muscle axis. As such, these patients are at an increased risk of both cancer therapy-related and age-related pathological outcomes; primary cardiovascular disease, exercise intolerance, and cancer-related fatigue. To date, however, therapeutic strategies that mitigate these negative effects within the human body have yet to be established. Previous work has demonstrated that dietary nitrate (NO₃⁻) supplementation can improve cardiac, vascular and cardiorespiratory exercise parameters, highlighting its potential therapeutic use in clinical populations. Therefore, we hypothesized that NO₃⁻ supplementation would improve both cardiac performance and exercise capacity. Methods: To date, 6 cancer survivors (57 ± 11 years) with a history of anticancer therapy completed a randomized, double-blind, crossover study with a single, acute-dose administration of NO₃⁻ or placebo (PL) [140 ml]. Transthoracic echocardiographic measures at rest were made to obtain left ventricular stroke volume. Patients performed a supine-cycling steady-state exercise test (30W) with measurements of arterial blood pressure, stroke volume, cardiac output, and a maximal-effort cardiopulmonary exercise test. Results: As intended, there was a statistically significant increase in plasma nitrite during the NO₃⁻ condition compared to PL (NO₃⁻ 1300 ± 963 µM vs. PL 111 ± 49 µM, respectively; P = 0.02). Additionally, we observed a decrease in relative oxygen uptake (VO₂) during steady-state exercise with NO₃⁻ compared to PL (NO₃⁻ 8.46 ± 2.2 vs. PL 8.98 ± 2.4 ml/kg/min; p = 0.01; Absolute VO₂: BRJ 0.64 ± 0.10 vs. PL: 0.68 ± 0.11 L/min; p = 0.01) indicating an improved exercise efficiency. Resting and steady-state arterial blood pressure, stroke volume, and cardiac output were not different between conditions. Furthermore, we did not observe any differences between conditions for peak relative VO₂ (NO₃⁻ 22.42 ± 3.86 vs. PL 23.14 ± 4.01 ml/kg/min; p = 0.23), total work done (NO₃⁻ 70.64 ± 29.5 vs PL 70.67 ± 30.71 kJ; p = 0.49), or for gross exercise efficiency (NO₃⁻ 5.23 ± 1.48 vs. PL 4.97 ± 1.41 kJ/L O₂; p = 0.14) during the maximal-effort cardiopulmonary exercise test. Conclusions: A single, acute-dose of inorganic nitrate supplementation in cancer survivors with a history of anticancer therapy enhanced steady-state exercise efficiency, but had no effect on exercise cardiac performance or peak exercise capacity.
Keywords: Cancer; Inorganic nitrate; Exercise; Anticancer therapy; Cancer survivor